2018
DOI: 10.3390/pharmaceutics10040216
|View full text |Cite
|
Sign up to set email alerts
|

Development of Parvifloron D-Loaded Smart Nanoparticles to Target Pancreatic Cancer

Abstract: Pancreatic cancer is the eighth leading cause of cancer death worldwide. For this reason, the development of more effective therapies is a major concern for the scientific community. Accordingly, plants belonging to Plectranthus genus and their isolated compounds, such as Parvifloron D, were found to have cytotoxic and antiproliferative activities. However, Parvifloron D is a very low water-soluble compound. Thus, nanotechnology can be a promising delivery system to enhance drug solubility and targeted deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…In another study, Silva et al reported the cytotoxic effect of ParvD in melanoma cell lines B16V5 and A375 with IC 50 values of 6.86 µM and 6.24 µM, following a 24 h period [12]. In comparison with the only reported study so far using the non-metastatic breast cancer cell line MCF7 [13] (IC 50 value of 35.10 µM), our results demonstrate that ParvD is highly cytotoxic for MDA-MB-231 cells, with an IC 50 value of 2.48 µM. This is an encouraging finding, since MDA-MB-231 cells exhibit a high level of resistance to an array of chemotherapeutic drugs [31].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In another study, Silva et al reported the cytotoxic effect of ParvD in melanoma cell lines B16V5 and A375 with IC 50 values of 6.86 µM and 6.24 µM, following a 24 h period [12]. In comparison with the only reported study so far using the non-metastatic breast cancer cell line MCF7 [13] (IC 50 value of 35.10 µM), our results demonstrate that ParvD is highly cytotoxic for MDA-MB-231 cells, with an IC 50 value of 2.48 µM. This is an encouraging finding, since MDA-MB-231 cells exhibit a high level of resistance to an array of chemotherapeutic drugs [31].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, future studies should be taken to develop adequate delivery systems that allow the targeting of this compound specifically to breast cancer cells. Such approaches were proposed by Silva et al (2016) and Santos-Rebelo et al (2018) using hybrid nanoparticles to target ParvD to melanoma and pancreatic cancer cells [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…They propose that the mechanism of action is associated with a decrease in mitochondrial membrane potential and the release of cytochrome c, and that it may be amplified by inhibition of extracellular signal-regulated kinases (ERKs) 1/2 signaling; they also suggest it may be caused by a mechanism dependent on intracellular ROS generation in leukemia cells [19]. Santos-Rebelo et al also report that Parv D obtained from P. ecklonii displayed a cytotoxic effect on pancreatic cell lines [42]. In the present study, it was found that of the four tested compounds, Parv D treatment induced the highest level of phosphorylated histone.…”
Section: Discussionmentioning
confidence: 99%
“…Osmunda regalis (Royal fern) [82]. Parvi loron D isolated from Plectranthus ecklonii via lash dry column chromatography exhibited antiproliferative effects against pancreatic cancer when evaluated against HaCat, BxPC3, Caco-2, MCF-7, Ins1-E and PANC-1 cell lines [53]. Aqueous extract of weed Solanum nigrum at concentration of 10 g/l caused 43% cytotoxicity in MCF7 cell line by inhibiting migration, suppression of hexokinase and pyruvate kinase [86].…”
Section: Therapeutic Potential Of Weeds Established In New Zealandmentioning
confidence: 99%